A court of specialists : judicial behavior on the UK Supreme Court - Hanretty, Chris (New York : Oxford University Press, 2020)
This book offers the first quantitative study of decision-making on the UK Supreme Court. Covering the court's first ten years, it examines all stages of the court's decision-making process-from permission to appeal to the decision on the final outcome. The main argument of the book is that judges' behavior is strongly affected by their specialism in different areas of law, and that the best way of understanding the UK Supreme Court is therefore to see it as a court of specialists.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 1, 2020).
Keywords: Great Britain. -- Supreme Court; Judicial process -- Great Britain; Judges -- Great Britain; Justice, Administration of -- Great Britain; Law; Laws of specific jurisdictions & specific areas of law